Probabilitas Pembayaran Kredit Tepat Waktu Menggunakan Algoritma Naive Bayes Pada Koperasi Serba Usaha Daruzzakah Rensing Lombok Timur - Nur Hidayati; Suhartini Suhartini (Fakultas Teknik Universitas Hamzanwadi, 2021)
In general, the notion of a cooperative is a business entity that is owned and managed by its members. Meanwhile, multi-business cooperatives are cooperatives whose business activities are in various economic aspects such as savings and loans, production, consumption and services, which consist of people or cooperative legal entities by basing their business activities on the cooperative principle as well as a people's economic movement based on the principle of kinship. This research took place in one of the cooperatives in the village of Rensing, East Lombok, with the cooperative name